2019
DOI: 10.1111/ejh.13229
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the room for improvement in management of acute promyelocytic leukemia

Abstract: Acute promyelocytic leukemia (APL) is highly curable. To achieve high cure rates, targeted therapy with retinoic acid (ATRA) must be started promptly at time of suspected diagnosis. Early death rates (EDRs, ≤30 days from diagnosis) differ markedly in patients treated on clinical trials compared to the general population. Objectives and methods: We used the comprehensive Danish National AcuteLeukemia Registry (DNLR) to investigate the incidence, treatment, EDR, and longterm clinical outcome in APL between 2000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…However, age was not a risk factor for OS in our study. Similar to our result, the Danish Registry was reported that while the age is not an independent risk factor for OS, the performance status of the patients is the main determinant of OS [34]. This may reflect the importance of performance status rather than the age during the treatment process.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, age was not a risk factor for OS in our study. Similar to our result, the Danish Registry was reported that while the age is not an independent risk factor for OS, the performance status of the patients is the main determinant of OS [34]. This may reflect the importance of performance status rather than the age during the treatment process.…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, we observed no improvement in 2-year OS rates from 2003-2009 to 2010-2016. Similarly, epidemiologic data demonstrated that there was no significant change in survival and remained relatively stable in recent years [16,34]. However, The International Consortium on Acute Promyelocytic Leukemia (IC-APL) demonstrated that the effort to recognize and treat APL early had been associated with significantly improved 2-year OS up to 80% in developing countries [35].…”
Section: Discussionmentioning
confidence: 99%
“…Another study investigated the incidence, treatment, ED rate and long term clinical outcome of APL patients. Twenty two of 41 deaths occurring in 122 APL patients were EDs which were primarily caused by intracranial hemorrhage, DIC, sepsis and multiorgan failure [8]. Contrasting to the life-threatening initial phase of APL, patients surviving this critical period have superior outcomes characterized by low relapse risk and high survival rates than other AML subtypes [9].…”
Section: Introductionmentioning
confidence: 99%
“…APL has evolved from being a deadly to a highly curable disease. [3][4][5][6][7][8][9][10][11][12][13] Despite advances in the treatment of APL, early death rates have remained relatively constant. Hemorrhagic complications are the most common cause of early death in patients with APL and remain a major challenge in the management of APL.…”
Section: Introductionmentioning
confidence: 99%
“…APL has evolved from being a deadly to a highly curable disease. 3–13 …”
Section: Introductionmentioning
confidence: 99%